Tablet Kompresi Langsung Ekstrak Etanol Daun Salam (Syzygium polyanthum) - Muhammad Gunawan; Suprianto; Samran; Cut Fatimah; Debi Melani; Sumardi (Jurnal Indah Sains dan Klinis, 2021)
Indonesia's natural wealth that is efficacious in suppressing cholesterol, hypertension, diarrhea, gastritis and blood sugar is one of the bay leaves (Syzygium polyanthum Wight.). Tablets are preparations that are practical to use, easy to produce, pack, and distribute. The research was directed to make tablets of bay leaf ethanol extract (EEDS) by direct compression. EEDS tablets were made into four formulas with various fillers of lactose and Avicel PH 102, each 200 mg : 135 mg A); 250 mg : 105 mg (B); 300 mg : 55 mg (C); and 350 mg : 5 mg (D). The study showed that all formulas met the preformulation test requirements and tablet evaluation, D as the best formula. EEDS is made into tablets by direct compression.